Antibiotic-induced alternations in gut microflora are associated with the suppression of immune-related pathways in grass carp (Ctenopharyngodon idellus) - Shi, Fei; Huang, Yao; Yang, Mingxuan; Lu, Zhijie; Li, Yanan; Zhan, Fanbin; Lin, Li; Qin, Zhendong (Frontiers in Immunology, 2022)
Gut microbiota play a vital role in fish health homeostasis. Antibiotics are known to alter microbial community composition and diversity; however, the substantial effects of antibiotics upon the gut microbiome with respect to immune-related pathways in healthy fish remain unclear. Accordingly, here we explored the impact of two antibiotics on the intestinal health, immune response, microbiome dynamics, and transcriptome profiles of grass carp. A two-week feeding trial was carried out in which the basal diet was complemented with enrofloxacin (10 mg/kg) or florfenicol (10 mg/kg). The results showed that: (1) Enrofloxacin and florfenicol both induced intestinal oxidative stress and reduced the digestive enzyme activity of grass carp. (2) High-throughput sequencing of 16S rDNA revealed that enrofloxacin but not the florfenicol treatment influenced gut microbiota diversity in grass carp by shifting α/β-diversity with more abundant pathogens detected. (3) Transcriptome profiling demonstrated that florfenicol down-regulated the immune-related pathways of grass carp, and the network analysis revealed that IgA was negatively correlated with certain pathogens, such as Shewanella and Aeromonas. (4) Antibiotic-induced alternations of gut core microbes were revealed via immune-related transcripts, as were lower mRNA expression levels of mucosal-related genes. (5) Apoptosis and histopathological changes were detected in the enrofloxacin- and florfenicol-treated groups compared with the control group. Overall, administering antibiotics will promote oxidative stress, cause intestinal flora dysbiosis, inhibit the mucosal immune system, and induce apoptosis in grass carp.